Thiazolidin-2-cyanamides derivatives as novel potent Escherichia coli β-glucuronidase inhibitors and their structure-inhibitory activity relationships - Tao-Shun Zhou; Bin Wei; Min He; Ya-Sheng Li; Ya-Kun Wang; Si-Jia Wang; Jian-Wei Chen; Hua-Wei Zhang; Zi-Ning Cui; Hong Wang (Taylor & Francis Group, 2020)
Gut microbial β-glucuronidases have the ability to deconjugate glucuronides of some drugs, thus have been considered as an important drug target to alleviate the drug metabolites-induced gastrointestinal toxicity. In this study, thiazolidin-2-cyanamide derivatives containing 5-phenyl-2-furan moiety (1-13) were evaluated for inhibitory activity against Escherichia coli β-glucuronidase (EcGUS). All of them showed more potent inhibition than a commonly used positive control, d-saccharic acid 1,4-lactone, with the IC50 values ranging from 1.2 µM to 23.1 µM. Inhibition kinetics studies indicated that compound 1-3 were competitive type inhibitors for EcGUS. Molecular docking studies were performed and predicted the potential molecular determinants for their potent inhibitory effects towards EcGUS. Structure-inhibitory activity relationship study revealed that chloro substitution on the phenyl moiety was essential for EcGUS inhibition, which would help researchers to design and develop more effective thiazolidin-2-cyanamide type inhibitors against EcGUS.